Inhalationsszintigraphie der Lunge mit dem neuen ultrafeinen Aerosol »Technegas« - Kropp, J.; Buhr, W.; Bockisch, A.; Grünwald, F.; Ruhlmann, J.; Hotze, A.; Biersack, H. J. (Nuklearmedizin - NuclearMedicine, 1989)
Evaporation of 99mTc-pertechnetate at about 2500° C on a carbon surface generates an ultrafine aerosol of labelled carbon clusters. Its particle size of about 2-5 nm enables the aerosol to behave similarly to a gas regarding the ability of penetration. After inhalation, the radioactive particles adhere to the walls of the respiratory bronchioli and alveoli. The high concentration of the radioactivity in the argon carrier gas makes it possible to record a scintigram after a single deep breath. We studied four healthy volunteers and 79 patients including 34 with a tentative diagnosis of pulmonary embolism, 20 with bronchus carcinoma, and 15 with various other lung diseases. Ten of these patients were infants, the youngest being nine months old. All patients also had a perfusion scintigraphy.